2012
DOI: 10.1089/gtmb.2011.0354
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus Infection in a Kashmiri Ethnic Female Population

Abstract: Human papillomavirus (HPV) infection is estimated to be the most common sexually transmitted infection and is one of the causal factors in cervical cancer. Understanding the epidemiology of this infection is an important step toward developing strategies for its prevention. Cervical samples from 210 healthy women with normal and abnormal cytomorphology were studied for the detection of HPV DNA by polymerase chain reaction (PCR), utilizing the two most commonly used consensus primer sets. The primers; MY09/MY11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…PCR. Both the samples were screened for the presence of HPV infection by PCR to amplify a 450-bp fragment from the conserved region in all HPV variants with MY09/MY11 primers: forward, 5'-CGTCCMARRGGAWACTGATC-3' and reverse, 5'-GCMCAGGGWCATAAYAATGG-3' as the reverse primer (34). PCR was performed using 200 ng of DNA along with dNTPs (0.2 mM each), Taq polymerase (cat.…”
Section: Characterizationmentioning
confidence: 99%
“…PCR. Both the samples were screened for the presence of HPV infection by PCR to amplify a 450-bp fragment from the conserved region in all HPV variants with MY09/MY11 primers: forward, 5'-CGTCCMARRGGAWACTGATC-3' and reverse, 5'-GCMCAGGGWCATAAYAATGG-3' as the reverse primer (34). PCR was performed using 200 ng of DNA along with dNTPs (0.2 mM each), Taq polymerase (cat.…”
Section: Characterizationmentioning
confidence: 99%
“…In some countries, cross-sectional and cohort studies have shown an interesting trend in the female age-specific distribution of HPV, whereby there is a first peak at a younger age (r 25 years) and a clear second peak among individuals aged 45 years or older (Munoz et al, 2004;Herrero et al, 2005;Franceschi et al, 2006;De Sanjose et al, 2007;Smith et al, 2008;Asiaf et al, 2012). The rationale behind the first peak, which comes soon after the onset of sexual relations, is higher levels of sexual activity with multiple partners and a low viral immunity.…”
Section: Epidemiology Of Human Papillomavirus Infectionsmentioning
confidence: 99%
“…In many studies, younger age was found to be associated with HPV infection. Asiaf A et al 8 found the highest prevalence of HPV infection in women below 30 years. Our study showed 57% positivity in the age group of <30 years.…”
Section: Discussionmentioning
confidence: 97%